1990
DOI: 10.1179/bjo.17.3.223
|View full text |Cite
|
Sign up to set email alerts
|

Glass Ionomers for Direct Bonding: An In Vitro Assessment

Abstract: An in vitro study was carried out resting the shear/peel bonding strength of brackets cemented with a glass-ionomer cement. It was found that the adhesive achieves its optimal bond strength at 24 hours. It is suggested that there is still scope for improvement of the material's mechanical properties and the use of prolonged clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
1

Year Published

1993
1993
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 13 publications
0
2
1
Order By: Relevance
“…The present study indicated that composite resins have a significantly higher bond strength 6.324 ± 0.795 MPa (for I hour) and 9.842 ± 1.058 MPa (for 24 hours) than either of the glass ionomer cements 7,8 Fuji Ortho (conditioned) has recorded bond strengths of 4.774 ± 0.786 MPa (for 1 hour) and 6.993 ± 1.281 MPa (for 24 hours) and Fuji Ortho (unconditioned) recorded a bond strength of 3.092 ± 0.572 Mpa (for 1 hour) and 4.047 ± 0.729 MPa (for 24 hours). 9 Fuji I (conditioned) has shown a slightly more (but statistically not significant) bond strength of 1.714 ± 0.407 MPa (for 1 hour) and 2.467 ± 0.297 MPa (for 24 hours) Pretreatment of enamel surfaces improved the magnitude of adhesion of glass ionomers, 10,11 though not significantly but the present study is not in agreement with the findings 12,13 who reported pretreatment of enamel with polyacrylic acid did not improve the bond strength of glass ionomers.…”
Section: Discussioncontrasting
confidence: 76%
“…The present study indicated that composite resins have a significantly higher bond strength 6.324 ± 0.795 MPa (for I hour) and 9.842 ± 1.058 MPa (for 24 hours) than either of the glass ionomer cements 7,8 Fuji Ortho (conditioned) has recorded bond strengths of 4.774 ± 0.786 MPa (for 1 hour) and 6.993 ± 1.281 MPa (for 24 hours) and Fuji Ortho (unconditioned) recorded a bond strength of 3.092 ± 0.572 Mpa (for 1 hour) and 4.047 ± 0.729 MPa (for 24 hours). 9 Fuji I (conditioned) has shown a slightly more (but statistically not significant) bond strength of 1.714 ± 0.407 MPa (for 1 hour) and 2.467 ± 0.297 MPa (for 24 hours) Pretreatment of enamel surfaces improved the magnitude of adhesion of glass ionomers, 10,11 though not significantly but the present study is not in agreement with the findings 12,13 who reported pretreatment of enamel with polyacrylic acid did not improve the bond strength of glass ionomers.…”
Section: Discussioncontrasting
confidence: 76%
“…ing molar bands [Brown, 1989], However, GIC can also be used to attach orthodontic brackets to teeth without the need of acid-ctching the enamel, thus replacing composite resins of Bis-GMA Type [Tavas, 1990]. The avoidance of the etching procedure with its mineral loss could be ad vantageous in many cases.…”
mentioning
confidence: 99%
“…Although conventional glass ionomer cements have shown inferior bond strengths compared to composite resins (12)(13)(14)(15)(16)(17), the recently developed resin-modified glass ionomer cements possess enhanced mechanical and physical properties. They provide clinically acceptable bond strengths if the bonding is performed onto wet enamel surfaces, as reported by a number of in vitro and in vivo studies (18)(19)(20)(21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%